High apolipoprotein AI concentrations are associated with lower mortality and myocardial infarction five years after coronary artery bypass graft surgery. - Skinner, J; Farrer, M; Albers, C; Neil, H; Adams, P (1999)
OBJECTIVE: To examine mortality and myocardial infarction five years after coronary artery bypass graft (CABG) surgery and the association with different lipid fractions and haemostatic, glycaemic, and demographic risk factors. SETTING: A regional cardiothoracic centre, Freeman Hospital, and the University Clinical Investigation Unit, Royal Victoria Infirmary, Newcastle upon Tyne, UK. DESIGN: 353 consecutive patients (297 male, mean age 57.2 years) undergoing first time CABG for stable angina were recruited to a prospective cohort study and studied to five years. MAIN OUTCOME MEASURES: All cause mortality, late cardiac mortality (beyond 30 days) alone and in combination with non-fatal myocardial infarction. Risk factor assessments before operation and 3, 6, 12, 24, and 60 months after surgery. For each laboratory variable a weighted mean for the period of exposure was calculated from the concentration at each time interval and the time between measurements. The distribution was divided into tertiles. RESULTS: 41 patients died (16 late cardiac deaths) and eight had a myocardial infarct. An adverse outcome occurred more frequently in the lower tertile of weighted apolipoprotein AI compared with the upper tertile. An adverse outcome was also more common in patients in the upper tertile of weighted total white blood cell count and less consistently so in patients in the upper tertile of the haemostatic covariates, factor VIIc and factor VIIIc. There was no association with other lipid fractions except for total mortality and apolipoprotein B (owing to low levels in five patients with carcinoma). CONCLUSIONS: Low apolipoprotein AI concentrations, but no other markers of an adverse lipid profile, were associated with mortality and myocardial infarction five years after CABG. Apolipoprotein AI is associated with paraoxonase, an enzyme located on high density lipoprotein, which may limit the oxidation of low density lipoprotein. An association between outcome and other covariates such as white cell count provides a credible pointer to inflammation mediating a component of cardiovascular risk.